Методи блокування сайтів - Семенченко, О. А. (ХНУРЕ, 2020)
In today's world, billions of people are facing a form of blocking when surfing the internet. Access to Internet content in countries is blocked using Internet service providers. Individual countries resort to technical restriction of access, usually for reasons of national security and to implement specific laws. Many users are also blocking access to resources that have been blocked for various reasons. By comparing all kinds of blocking and bypassing the blocking of sites, I brought them a classification. Also, for each criterion I have assigned my coefficient.